Pelatihan Sertifikasi Microsoft Office Specialist (MOS) Bagi Siswa-Siswi SMK Islam Malahayati Jakarta - Firman Noor Hasan; Djeli Moh Yusuf; Fayakun Kun (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Educators who have competence in certain areas of expertise will guide their students to have competency in those areas of expertise. Competency in the field of expertise is obtained through a certification exam. The main purpose of competency certification is to ensure a person is competent in their area of expertise through the learning stage as well as the work experience stage. Certifications are usually issued by institutes, organizations, or professional associations that oversee certain professional competencies. This activity is motivated by the following: (1) In general, teachers and students do not know about the importance of competency certification, which is not only recognized nationally but is also recognized on an international scale. (2) In general, teachers and students do not know how to use Microsoft Office tools in accordance with international standards (SI). (3) There are still many students who do not have competency certification, both at the national and international levels. (4) Students do not know the international competency certification exam methods that use the CBT system and simulators that are connected in real-time. This community service activity is in the form of a training method for Microsoft Office Specialist International competency certification, which is divided into several stages. The results of the evaluation questionnaire filled out by the participants resulted in 52.23% feeling very satisfied, while 44.06% of the participants felt agreeable, satisfied, and helped through community service and mentoring activities.